THE INFLUENCE OF TRAINING ROLES, SELF-EFFICACY, CREATIVE PROBLEM-SOLVING ON IMPROVING EMPLOYEE PERFORMANCE - Afifah Gusti Layyinah; Didik Subiyanto (IAIN Surakarta, 2022)
Employee performance is an essential component of comparing a company with its employees to achieve productive and efficient results. It can be found in any organization, especially in the Bantul Trade Service. This quantitative study aims to find information about training, self-efficacy, creative problem solving on the performance of employees in the Bantul Trade Service. At the same time, 57 employees were involved in the study, with 34 state civil apparatus and 30 contract employees. The research procedure used is a sample saturated with the amount available. The information collected by the questionnaire is then processed and evaluated using SPSS 24, a descriptive statistical system. The findings of this study showed that the training did not have a positive or significant impact on the performance of employees at the Bantul trade service. The absence of training offered by the Department to each employee affects this issue. Self-efficacy and creative problem solving, on the other hand, have a beneficial and considerable impact on employee performance. To improve employee performance at the Bantul Trade Office, training, self-efficacy, and creative problem solving must be maximized through suitable training and education for staff.